2017
DOI: 10.3126/jcmsn.v12i4.16374
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of sonographic fetal weight estimation in a tertiary care hospital in Bharatpur, Nepal

Abstract: Background & Objectives: Among the var ious methods used in the estimation of intrauterine fetal weight, sonographic fetal weight estimation is the one and has become an important component of antenatal care. The study was conducted with objective to assess the accuracy and reliability of ultrasound estimation of fetal weight in women with a singleton term pregnancy. Materials & Methods: This was a prospective cross-sectional study of 120 women with singleton term pregnancies. Ultrasound estimated fetal weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
4
3
0
Order By: Relevance
“…This implies that when it is indicated, ultrasound should be used to estimate the fetal weight for the purposes of planning delivery and monitoring of the fetus. Similar findings have been observed by other studies [2, 6, 12].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This implies that when it is indicated, ultrasound should be used to estimate the fetal weight for the purposes of planning delivery and monitoring of the fetus. Similar findings have been observed by other studies [2, 6, 12].…”
Section: Discussionsupporting
confidence: 93%
“…The absolute mean error of estimation of 258.52 recorded in our study is comparable to observed values by Prasad et al in Nepal [12]. The mean absolute percentage of 7.56% is comparable to 8.76%, 7.2%, 7.7% reported by Prasad et al [12], Lafont et al [13], Colman et al [14], and Houzé de l'Aulnoit et al [15], respectively. It is also within the 6–12% reported in the literature [4].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are comparable with mean percentage error and mean absolute percentage error of ultrasound fetal weight estimations were 1.9±11.4% and 8.8±7.5% respectively in the study done by Prasad et al 15 These results are also consistent with previously observed findings that the mean absolute percentage error of predicting birth weight varies from 6% to 12% of actual birth weight. 12 The percentage of estimates within ±10% of the actual birth weight was found to be 67.3% which is comparable with the percentage of estimates within ±10% of the actual birth weight was found to be 65% in the study done by Prasad et al 15 These results are also consistent with what have been previously observed that 40-76% of the estimates were within 10% of actual birth weight. 12 The ultrasound estimated fetal weight (EFW) had a strong positive correlation with actual birth weight (ABW) of the newborns (r = 0.58, p <0.001).…”
Section: Discussionsupporting
confidence: 92%
“…Macrosomia refers to the weight of a newborn being more than 4000g within one hour after birth. The prenatal diagnosis of macrosomia will provide guidance for medical staff to make correct treatment during delivery, thus reducing the incidence of maternal and infant obstetric complications [9]. In addition, the accurate estimation of a fetus whose birth weight is less than 2500g is also conducive to early prenatal diagnosis of intrauterine growth retardation and improvement of maternal and infant pregnancy outcomes [10].…”
Section: Discussionmentioning
confidence: 99%